Conversion of Heat Energy from Cooling Water of Diesel Engine to Electrical Energy Using Thermoelectric Generator - Albana, Muhammad Hasan (Makara Journal of Technology, 2018)
This research objective is to convert heat from the radiator fluid of a diesel engine to electrical energy by utilizing a thermoelectric generator (TEG). The TEG consists of 20 semiconductors (TE modules) and is equipped with a heat sink. The research shows that using the TEG, the heat of radiator fluid can be converted to electrical energy, although the electricity generated is small. The maximum electrical voltage generated by the TEG when modules were connected in series was 10 volts. When the TE modules were connected in parallel and series-parallel, the maximum voltages generated were 2.11 and 2.53 volts, respectively. The maximum electric current generated by the TEG when the modules were connected in series-parallel was 128 mA. When the modules were connected in series and parallel, the maximum electrical currents generated were 108.3 and 69.7 mA, respectively. The series circuit is the best choice for the TEG because it produced the highest electrical power. The TEG efficiency in this study was 5%–7.1%. The voltage and electric current generated by the TEG will be higher if the temperature difference between the hot and cold sides of the semiconductor is higher. The use of this TEG did not reduce the performance of the test engine cooling system or radiator system.